Phenoglad: um modelo de simulação do desenvolvimento em gladíolo - Uhlmann, Lilian Osmari (2016)
Crop simulation models are important tools to help farmers in planning management practises and flowering time of cut flowers, like gladiolus (Gladiolus x grandiflorus Hort.). The objective of this study was to develop a robust gladiolus phenology model, named PhenoGlad, for field applications. The model describes the timing of developmental stages, including harvest point, the vase life of gladiolus spikes and the low (chilling) and high (heat) temperature effects on spike quality. The gladiolus developmental model simulates gladiolus phenology using a non-linear temperature response function and, by accumulating daily development rates considering three main phases: corms sprouting phase, vegetative phase, and reproductive phase. Data from nine field experiments conducted during five years (2011 2015) in three locations across the Rio Grande do Sul State and in one location in Santa Catarina State, Brazil, were used. These cultivar x planting dates x years x locations experiments provide a rich data set for calibrating and evaluating the gladiolus model. The PhenoGlad model accurately simulated the dynamics of leaf development, final leaf number and the timing of developmental stages using genotype-specific coefficients that can be estimated from thermal time. The performance of the model was improved when the simulations started from emergence compared to when simulations started at the planting date. PhenoGlad showed good stability among cultivars, planting dates, years and sites, with an RMSE of 0.5 leaves for leaf development and final leaf number, 6.5 to 5.0 days for the date of reproductive developmental stages when the model started from planting or from emergence, respectively, and 1.3 days for simulating the vase life of harvested spikes. PhenoGlad was also efficient in predicting the effects of chilling and high temperatures damage on florets.